Absorption and degradation of sulfated polysaccharide from pacific abalone in in vitro and in vivo models. (August 2017) - Ai, Chunqing; Ma, Na; Sun, Xiaona; Duan, Mengmeng; Wu, Sufeng; Yang, Jingfeng; Wen, Chengrong; Song, Shuang
Highlights: Absorption and metabolisms of sulfated polysaccharide were analyzed. Human digestive juices had no effect on AGSP molecular weight. Biological activities of AGSP could attribute to the modulation of gut microbiota. Abstract: Various bioactivities of sulfated polysaccharides have been demonstrated, but the exact mechanisms involved are still unclear, which can be mainly attributed to a lack of recognition of polysaccharides metabolism in vivo . To define action mechanisms of sulfated polysaccharide from pacific abalone (AGSP), its metabolic characteristics were first evaluated in a mice model. The result showed that AGSP was hard to be absorbed into plasma, and most might be excreted from the body via feces. The in vitro models showed that human digestive juices had no effects on AGSP, and AGSP could exert its bioactivities by modulating the gut microbiota composition. It was noteworthy that small AGSP fragment was also hard to be absorbed by the body. In summary, this study demonstrated that various bioactivities of AGSP could be mainly attributed to the modulation of the gut microbiota rather than direct action on body organs far away from the digestive tract.